Reverse Phase HPLC Estimation of Tamsulosin Hydrochloride in Bulk and in Pharmaceutical Dosage Forms - GOWRI SANKAR, D.; DURVASA RAO, B.; SAI KISHORE, V.; MURTHY, T.E.G.K. (Asian Journal of Chemistry, 2010)
A simple, precise, rapid, reproducible and selective reverse phase HPLC method has been developed for the estimation of tamsulosin hydrochloride in bulk and pharmaceutical dosage forms. The analyte was resolved by using a mobile phase (acetonitrile, methanol and water in the ratio 37:13:50) at a flow rate of 1 mL/min. on an isocratic HPLC system consisting of LC-10 at liquid pump, SPD-10AVP UVVisible detector, an ODS C-18 RP column (4.6 mmL.D x 250) at the wavelength of 232 nm. The linearity range is found to be 2-10 μg/mL.